Image Does Matter Personal Style Vs Professional Image - Mia Angeline (Humaniora, 2013)
In today’s professional world, one of the most widely ethical topics discussed is about employee’s personal style, that is unique, but cannot be categorized as professional. Personal style is considered as one of the rights of employees to express themselves and is not be regulated by the company. However, image of the company is reflected in the personal style and appearance of its employees. Therefore, this article examines the importance of personal style and the impacts on professional image as perceived by executives from various industries in Jakarta. Data were collected through interviews and literature. Results showed personal style is very important in the industry related to customer relations and retention, as well as personal style has a significant impact on the professional image of the individual and the company.